THE KAMI CULT IN THE JAPANESE FOLK RELIGIOUS TRADITION - Hüsamettin KARATAŞ (Fırat University, 2020)
The ancient religious tradition of the Japanese, the Shintoism, by another words Kami-no miçi, has a structure shaped by the religious beliefs and practices of the Japanese people. This tradition is essentially a national religion unique to the Japanese. As an expression of the Japanese folk religion tradition, Shintoism emphasizes the ancestral cult; It is a religion that includes politeist, naturalist and anthropomorphic characters. For the Japanese, believing in the Kami is actually acting in accordance with their will. This is a situation that can be explained by spirituality beyond the tradition for the Japanese. Indeed, the “Kami Cult” for the Japanese is a phenomenon in all areas of life. Therefore, believing in the families and leading a life as they want is the greatest ideal. At the end of this ideal, of course, it is possible to be as great as a Kami or as respected as extraordinary beings. In this study, the "Kami cult" in the Japanese folk religion tradition has been handled and examined in some ways. In this context, it was especially focused on how the Japanese understood and how they made sense of the Kami that they respect with fear. Because the Kamis or the Kami’s social realms contain elements that will amaze and amaze human beings. However, Kami’s are the central figure of mysterious phenomena, terrible natural phenomena that attract people's curiosity. At the same time, for Japanese people, Kami’s are another name for respect, devotion, tabasbus and worship, beyond being primitive and supernatural beings.